IDENTIFICATION OF MODAL PARAMETERS OF VIBRATING STRUCTURES WITH UNKNOWN ORSTOCHASTIC EXCITATION - Amaro Baldeón, Roberto (2005)
The Vector Autoregressive Moving Average (VARMA) Model is used to identify dynamical characteristics of a structural system in the presence of noise. In order to estimate the parameters of the VARMA Model, the Spliid’s fast algorithm is used. To determine the modal parameters the companion matrix is built with the autoregressive part of the VARMA Model. The performance of this method here discussed is presented by means of simulations, using three degrees of freedom mass-dampingstiffness vibrating system.